Improving voltage stability on 220kv electrical network of the Vietnam Southwest region - Nguyen, Nhân Bổn; Nguyen, Tấn Chiếm (Journal of Technical Education Science, 2019)
Voltage stabilization is the ability to maintain the voltage across all nodes in the system within a given limit. The electrical system will become unstable when it comes to a sudden increase in load or changes in system parameters. These sessions will make the process of voltage drop occur and the most severe is likely to cause voltage collapse, power failure in each region, each region, causing great economic losses. It can affect the political and social. In order to improve the voltage stability for Vietnam's power system in general and the 220 kV power grid in the South West region in particular, there are pieces of research to find the optimum location for the reactive power compensation equipment SVC. However, the analysis will ignore the economic factors that focus only on technical factors. Studying and calculating using the grid diagram of the South West region and the data expected to 2020. The results of calculating and analyzing PV characteristics are investigated through specialized software PSS/E 33.